2004
DOI: 10.1021/ol036496h
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Carbon−Carbon and Carbon−Sulfur Cross-Coupling of Boronic Acids with 3,4-Dihydropyrimidine-2-thiones

Abstract: Direct microwave-assisted Pd(0)-catalyzed/Cu(I)-mediated carbon-carbon cross-coupling of 3,4-dihydropyrimidine-2-thiones and boronic acids under Liebeskind-Srogl conditions leads to 2-aryl-1,4-dihydropyrimidines in moderate to high yield. In contrast, Cu(II)-mediated reaction of the same substrates leads to carbon-sulfur cross-coupling. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(65 citation statements)
references
References 29 publications
1
61
0
3
Order By: Relevance
“…Several research groups have reported other high-speed microwave-assisted transition-metal-catalyzed transforma-tions, such as Suzuki, [279] Heck, [280] Sonogashira, [281] Negishi, [282] and Liebeskind-Srogl reactions, [283] BuchwaldHartwig aminations, [284] and related reactions. [285] Bahn and Adolfsson have demonstrated that functionalized 2,5-dihydropyrroles can be obtained by microwavemediated ruthenium-catalyzed ring-closing metathesis (RCM).…”
Section: Addendummentioning
confidence: 99%
“…Several research groups have reported other high-speed microwave-assisted transition-metal-catalyzed transforma-tions, such as Suzuki, [279] Heck, [280] Sonogashira, [281] Negishi, [282] and Liebeskind-Srogl reactions, [283] BuchwaldHartwig aminations, [284] and related reactions. [285] Bahn and Adolfsson have demonstrated that functionalized 2,5-dihydropyrroles can be obtained by microwavemediated ruthenium-catalyzed ring-closing metathesis (RCM).…”
Section: Addendummentioning
confidence: 99%
“…An interesting example is the protocol described by Lengar and Kappe; [98] the authors demonstrated that microwave irradiation can tremendously speed up the sluggish thioether-boronic acid Liebeskind-Srogl-type couplings. Moreover an unprecedented novel carbon-carbon cross-coupling reaction was discovered involving thioamides and boronic acids.…”
Section: Miscellaneousmentioning
confidence: 99%
“…[100] Interestingly, it was demonstrated that although the catalytic Pd 0 /Cu I system resulted solely in carbon-carbon bond formation, the use of stoichiometric amounts of Cu II under an air atmosphere resulted in carbon-sulfur bond formation (Scheme 76). [98,99] It has been shown that both types of thioamide cross-couplings are orthogonal to the traditional base-catalysed Suzuki-Miyaura cross-coupling of aryl halides with boronic acids. Scheme 76.…”
Section: Miscellaneousmentioning
confidence: 99%
“…They have been recognized as important heterocyclic compounds due to their diverse biological activities such as Tie-2 kinase inhibitors [2], HIV-1 inhibitor [3], antimalarial [4] secretive adenosine A1 receptor antagonist [5], anticancer [6,7], analgesic [8], and cardiovascular [9] activities. Furthermore, it has been found that 3,4-dihydropyrimidin-2(1H)-ones (DHPMs) have interesting multifaceted pharmacological profile as hepatitis B virus (HBV) replication inhibitors [10][11][12]. Moreover, the pyrimidine ring in an organic molecule also shows prominent activity as antagonist of both a1-adrenergic and serotonin-S2 receptors [13].…”
Section: Introductionmentioning
confidence: 99%